1999
DOI: 10.1111/1467-9817.00078
|View full text |Cite
|
Sign up to set email alerts
|

Training in phonological strategies improves Chinese dyslexic children’s character reading skills

Abstract: This study investigated Chinese dyslexic children's efficiency in employing phonological strategies (i.e. the use of orthography-phonology correspondence rules) in reading and the effectiveness of training phonological strategies in improving Chinese dyslexic children's reading performance. An Experimental Group of 15 Chinese dyslexic children received a five-day intensive training in phonological strategies while a comparable Control Group did not. The results showed that Chinese dyslexic children did not use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 25 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…Training in orthographic skills generally shows its effectiveness in promoting children's reading performance in Chinese. Studies found that explicit instructions that reminded learners of the radical structures enhanced the memorization of Chinese characters (e.g., Ho, Wong, & Chan, 1999;Taft & Chung, 1999;Wang, Liu, & Perfetti, 2004); learning the functions and regularity of phonological radicals of Chinese characters helped word reading (Ho & Ma, 1999); and explicit teaching of the functions of semantic radicals of Chinese characters also helped learners to extract semantic information from the semantic radical of the given characters (Wang, Liu, & Perfetti, 2004).…”
Section: Training Of Metalinguistic Skills In Chinesementioning
confidence: 99%
“…Training in orthographic skills generally shows its effectiveness in promoting children's reading performance in Chinese. Studies found that explicit instructions that reminded learners of the radical structures enhanced the memorization of Chinese characters (e.g., Ho, Wong, & Chan, 1999;Taft & Chung, 1999;Wang, Liu, & Perfetti, 2004); learning the functions and regularity of phonological radicals of Chinese characters helped word reading (Ho & Ma, 1999); and explicit teaching of the functions of semantic radicals of Chinese characters also helped learners to extract semantic information from the semantic radical of the given characters (Wang, Liu, & Perfetti, 2004).…”
Section: Training Of Metalinguistic Skills In Chinesementioning
confidence: 99%
“…In cases when phonetic components provide only partially reliable phonological information, Chinese children typically are able to use subcharacter information to read unfamiliar words (He, Wang & Anderson, 2005 ;Ho & Ma, 1999). However, dyslexic children with poor phonological awareness would face greater challenges, when asked to read low-frequency or irregular words, than average readers at the same reading level (Ho, Chan, Tsang, Lee & Chung, 2006).…”
Section: Phonological Deficit In Developmental Dyslexiamentioning
confidence: 99%
“…Dyslexic Chinese children have been shown to have deficits in processing phonological information just like their counterparts who learn to read in alphabetic languages (Ho, Law, & Ng, 1998;So & Siegel, 1997). Interestingly, in a recent st udy Ho and Ma (1999) demonstrated that training in phonological strategies is effective in improving dyslexic Chinese children s reading performance, as well.…”
Section: L1-based Cross-linguistic and Cross-orthography Research In mentioning
confidence: 99%